Analysis and comparison of energy consumption and energy simulation in Rimaskóli Primary School - Tenley Addison Propst 1996- (2021)
As the world moves towards sustainable energy resources while dealing with the climate change and energy security, it is important to investigate the ways in which energy is consumed. In Iceland particularly, geothermal energy is abundant and utilized for district heating within buildings. However, in attempts to make the energy system even more sustainable, there must be analysis of energy usage and potential sources of energy losses in order to find ways to prevent energy waste. Through conduction of a case study analysis, the heat energy consumption of Rimaskóli primary school is researched. With measured data on the return hot water temperature, inflow rate, and electricity consumption, an estimate of the energy consumption patterns was analyzed. Using design and utility drawings along with the measured data, a building simulation model is constructed using IDA-ICE simulation software. Heat energy consumption by radiators were modeled in the program, displaying results 12% higher than the daily measured results. To gain a further understanding of building energy performance, the control mechanisms for radiators and window openings were adjusted. While automatic radiator and window control displayed the highest heat energy consumption values compared to other variations, the indoor air temperature achieved is closest to the thermal comfort setpoint of 21 ̊C. Changes to window glazing showed that a reduced U-value for windows will decrease the heat loss experienced by 32.5%. The absense of an exhaust ventilation system was simulated, yielding reduced heat energy consumption and heat loss. The results indicate where further research on the measured data should be focused and its impact on the modeled results. Á meðan heimurinn færist í átt að nýtingu sjálfbærra orkuauðlinda þar sem tekist er á við bæði loftslagsbreytingar og orkuöryggi, þá er mikilvægt að kanna með hvaða hætti orku er neytt. Á Íslandi er jarðhiti mikilvæg auðlind sem nýtt er til húshitunar. Til þess að gera orkukerfið enn sjálfbærara og finna ...